Innovative applications of silicon dioxide nanoparticles for targeted liver cancer treatment - Fu, Tiantian; Duan, Boshi; Sun, Peng; Ma, Wei; Wang, Tianzuo; Wang, Tianyou; Tong, Zhuang; Wang, Yue (Frontiers in Bioengineering and Biotechnology, 2025)
Liver cancer remains a major global health challenge, characterized by high mortality and limited treatment efficacy. Conventional therapies, including chemotherapy, immunotherapy, and viral vectors, are hindered by systemic toxicity, drug resistance, and high costs. Silica nanoparticles (SiO2NPs) have emerged as promising platforms for liver cancer therapy, offering precise drug delivery, stimuli-responsive release, and integrated diagnostic-therapeutic capabilities. This review critically examines the potential of SiO2NPs to overcome these therapeutic limitations. Notable advances include their high drug-loading capacity, customizable surface modifications, and dual-responsive systems (pH/redox/NIR-II) that enable >90% tumor-specific drug release. Preclinical studies have demonstrated synergistic efficacy in combination therapies. Additionally, theranostic SiO2NPs enable MRI-guided tumor delineation and real-time treatment monitoring. Despite promising results, challenges remain in long-term biosafety, scalable synthesis, and regulatory compliance. Early-phase clinical trials, including those using NIR-II-responsive platforms, highlight their translational potential but underscore the need for further validation of toxicity profiles and manufacturing standards. Future research should focus on optimizing combinatory treatment strategies, scaling up production, and aligning with evolving regulatory frameworks. By bridging nanomaterial innovation with clinical applications, SiO2NPs offer unparalleled potential for advancing precision oncology in hepatocellular carcinoma.